Perception of Money Politics, Hoax and Sara Issues in 2019 Elections - Umam, Syamsul (Tribakti: Jurnal Pemikiran Keislaman, 2020)
Research on students' perceptions about money politics, hoaxes and sara issues in the 2019 elections in Tulungagung Regency is motivated by the high practice of money politics in various political events, from local elections to elections, on the basis that researchers try to photograph how students' understanding of money politics, hoaxes and the issue of sara, this study uses a qualitative method that is collecting data obtained from the results of interpretation in the field, this study also portrays the implications of money politics, hoaxes, sara issues to influence the choice of students in Tulungagung Regency in the 2019 Election, it is seen from the results Researcher's interviews with a number of informants resulted in students' understanding of money politics, hoaxes and sara issues being very good, students understanding the understanding of money politics in detail, even when in the construction of student money politics understanding in Tulungagung Regency almost approached the existing understanding in the law of the government. You do not stop their students also understand various phenomena of money politics and their modes, students' understanding of hoaxes with content issues is also quite good because almost all students define hoax details with examples and models of their stories, students also assume that spreading the issue of care in the general election contestation is considered to be very dangerous and for the continuation of democratic life in Indonesia which causes divisions and disintegration.